2013
DOI: 10.14233/ajchem.2013.15302
|View full text |Cite
|
Sign up to set email alerts
|

Decorative Coatings of Crystallite Type on Metallic and Non-metallic Surfaces

Abstract: The results of decorative coatings of 'crystallite' type on metallic and non-metallic surfaces are presented in this work. We propose the low-temperature chemical method that allows receiving the "crystallite" pattern with a preliminary assessment of decorative coating quality on all, including non-metallic materials. For this, at first a product is dipped for a few seconds into the saturated solution of copper salt at the temperature of 80-90 ºC for metals and 60 ºC for polymeric materials. At drying the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The concentration of CuSO 4 g/l is optimal since it allows the introduction on the surface of the product of a sufficient amount of copper phosphide, moreover, it does not result in the formation of crystals of copper sulphate leading to inhomogeneity of the coating [20][21][22]. Calculations showed that the film thickness of the solution remaining on the surface of the sample was 50-70 m. The kinetic of the conversion process, measured through the volume of adsorbed phosphine, is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of CuSO 4 g/l is optimal since it allows the introduction on the surface of the product of a sufficient amount of copper phosphide, moreover, it does not result in the formation of crystals of copper sulphate leading to inhomogeneity of the coating [20][21][22]. Calculations showed that the film thickness of the solution remaining on the surface of the sample was 50-70 m. The kinetic of the conversion process, measured through the volume of adsorbed phosphine, is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several coating techniques were investigated for the accumulation of metallic particles of the Cu alloys on insulating substances, for example, vacuum metallization [5], laser sputter coating or vapor deposition, and chemical coatings [6]. Every method has several advantages and disadvantages, for example, toxic reducing agents are known to be employed during chemical coatings [7].…”
Section: Introductionmentioning
confidence: 99%
“…Various coating methods were developed for deposition of antimicrobial metals of copper subgroup on dielectric materials such as vacuum metallization [16][17][18][19], vapor deposition or laser sputtering [20][21][22][23], chemical deposition [23][24][25][26][27][28]. There are advantages and disadvantages for each method, for example, for chemical deposition sometimes toxic reducing agents are employed [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%